Clavulanic acid separation on fixed bed columns of layered double hydroxides: Optimization of operating parameters using breakthrough curves. Issue 4 (April 2016) - Forte, Marcus Bruno Soares; Taviot-Guého, Christine; Leroux, Fabrice; Rodrigues, Maria Isabel; Maugeri Filho, Francisco
Graphical abstract: Highlights: Adsorption breakthrough curves of CA in a fixed-bed column of LDHME adsorbents. Response surfaces enabled identification of the best column operating conditions. Factorial design technique is an efficient tool for process optimization. Good separation of CA from the amino acids tyrosine and proline was observed. The LDHME adsorbent was shown to be an excellent alternative for CA purification. Abstract: The adsorption of clavulanic acid (CA) in a fixed-bed column of layered double hydroxides (LDHME ) was investigated. Breakthrough curves were obtained experimentally and the system was evaluated with regards to column operation time, efficiency and productivity as functions of simultaneous variations of superficial velocity ( v z ) and bed height ( L ) using a central composite rotatable design (CCRD). At the optimized condition ( v z  = 1.00 cm/min and L  = 6.5 cm), the responses were: 46 min, 146 min, 100 min and 13 kg/h cm 3, for breakthrough time ( tb ), exhaustion time ( te ), the difference te  −  tb and productivity ( P ), respectively. These results represent no change in tb, but a 50% decrease of te, 40% decrease of ( te  −  tb ) and 38% increase of P, which is advantageous for the process. The factorial design technique was shown to be an efficient tool for assessing factor influences and was effective in optimizing the column operating conditions. Good separation of CA from the amino acids tyrosine (TYR) and proline (PRO) was observed in fixed bed columns. The LDHME adsorbent was shown to be an excellent alternative for CA purification.